Heat transfer of single droplet or droplet train impingement on a superheated surface - Li, Junru (2017)
The spray and jet cooling techniques are promising solutions for the effective thermal management of high power-density electronics. In this project, three basic physics models of the fluid impingement cooling, namely the single droplet impingement model, the droplet train impingement model and the jet impingement model, will be thoroughly studied to gain useful insights into the topic. After reviewing previous literatures, following research gaps were found: (1) the impact force due to the liquid impingement; (2) connections between different impingement models; (3) influence of the function generator frequency on impingement heat transfer characteristics. Therefore, two main focus, namely the impact force and heat transfer characteristics of three different impingement models, are selected for this study. To measure the tiny impact force (~10e-5 N), a test rig which can intensify small forces is designed. The impact force of the single droplet impingement is measured to be 9.645e-6 N and 8.022e-6 N for the wall temperature below and above the Leidenfrost point. Moreover, conductive heat transfer data analysis methods are proposed to obtain heat transfer rate Q, heat flux q and heat transfer coefficient h from the transient temperature difference ∆T_us measured by thermocouples inserted into the substrate and the impingement area measured from high-speed camera pictures. The method is proved practical since, with all other conditions fixed, different ∆T_us at the same wall temperature (due to various heating speeds) are corrected to coincide with each other. Furthermore, the influence of the wall temperature and the function generator frequency on heat transfer characteristics of different impingement models are studied over a wide wall temperature range of 140~240 °C and frequencies of 28 kHz, 40 kHz, 56 kHz and unknown frequency (function generator turned off and irregular-sized droplet train formed). With increasing wall temperature, Q of both droplet train and jet impingement continuously drops, while q and h of the droplet train impingement (40 kHz) increase to maximum value of around 1.72e8 W/m^2 and 1.84e6 W/(m^2 K) respectively. For regular-sized droplet train, with increasing frequency, Q decreases and q and h increases. If the droplet train becomes irregular (with the function generator turned off), Q will increase. If the function generator is suddenly turned on during the jet impingement, the stable jet will become unstable, and Q will suddenly decrease for vertical jet with a wall temperature above the Leidenfrost point. As for the angled jet, with the transition from stable to unstable jet, Q will decrease if the wall temperature is below the Leidenfrost point and increase if the wall temperature is above the Leidenfrost point. Last but not least, more works regarding the influence of the wall temperature on the single droplet impact force and calculation of q and h of irregular-sized droplet train impingement are to be carried out in the future.